2014
DOI: 10.3892/ol.2014.2426
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer metastasis to mediastinal lymph nodes without liver or lung involvement: A case report

Abstract: Colon cancer is the second most common type of cancer in females and the third in males, worldwide. The most common sites of colon cancer metastasis are the regional lymph nodes, liver, lung, bone and brain. In this study, an extremely rare case of colon adenocarcinoma with extensive metastasis to the mediastinal lymph nodes without any other organ involvement is presented. A 44-year-old Caucasian male presented with abdominal pain, a change in bowel habits, melena and weight loss. Colonoscopy revealed a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Typically, the most common sites of colon cancer metastasis are regional lymph nodes, liver, lung, bone and brain, with ours demonstrating an extremely rare pattern of colon cancer metastasis. 4 The novelty of this case revealed metastatic involvement to the left supraclavicular node without end organ involvement, ie (liver, lungs) conjugated with the patients carcinomic history.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Typically, the most common sites of colon cancer metastasis are regional lymph nodes, liver, lung, bone and brain, with ours demonstrating an extremely rare pattern of colon cancer metastasis. 4 The novelty of this case revealed metastatic involvement to the left supraclavicular node without end organ involvement, ie (liver, lungs) conjugated with the patients carcinomic history.…”
Section: Introductionmentioning
confidence: 56%
“…2 Mucinous carcinoma is defined according to WHO as a subtype of colorectal carcinoma (CRC) with mucin lakes comprising at least 50% of the tumor mass. 3 Distal nodal metastatic colon cancer is uncommon and metastasis of CRC to the left supraclavicular lymph node, also known as Virchow’s node, is extremely rare without signs and symptoms of metastatic organ involvement 4,5…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, CT scan revealed pathological mediastinal adenopathies. In the case reDuplication Esophageal Cyst ported by El-Halabi et al [1] , the definitive diagnosis was made by EUS-guided FNA, which revealed multiple, enlarged, rounded, homogeneous, and hypoechogenic subcarinal lymph nodes. Musallam et al [2] presented a patient with solitary enlarged right paratracheal lymph node, positive on fluor-18-deoxyglucose positron emission tomography scan, who underwent mediastinoscopic biopsy, which revealed metastatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports of solitary metastatic mediastinal lymph node of colorectal cancer (CRC) without any other organ involvement [1,2] . Posterior mediastinal cystic lesions represent 15-20% of all primary posterior mediastinal masses and include bronchogenic, pericardial, neuroenteric, and duplication esophageal cysts (DEC) [3] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, we find that MDR seems to be related to sorcin. Sorcin is a calcium-binding protein that is highly expressed and induces MDR in several cancer patients 15,16. Sorcin affects the functions of P-gp by the regulation of cellular calcium levels and the phosphorylation of P-gp.…”
Section: Introductionmentioning
confidence: 99%